Thalamo-Nucleus Accumbens Projections in Motivated Behaviors and Addiction - De Groote, Aurélie; de Kerchove d’Exaerde, Alban (Frontiers in Systems Neuroscience, 2021)
The ventral striatum, also called Nucleus Accumbens (NAc), has long been known to integrate information from cortical, thalamic, midbrain and limbic nuclei to mediate goal-directed behaviors. Until recently thalamic afferents have been overlooked when studying the functions and connectivity of the NAc. However, findings from recent studies have shed light on the importance and roles of precise Thalamus to NAc connections in motivated behaviors and in addiction. In this review, we summarize studies using techniques such as chemo- and optogenetics, electrophysiology and in vivo calcium imaging to elucidate the complex functioning of the thalamo-NAc afferents, with a particular highlight on the projections from the Paraventricular Thalamus to the NAc. We will focus on the recent advances in the understanding of the roles of these neuronal connections in motivated behaviors, with a special emphasis on their implications in addiction, from cue-reward association to the mechanisms driving relapse.